Excess turnover and employment growth: firm and match heterogeneity - Mário Centeno; Carla Machado; Álvaro A. Novo (Institute for the Study of Labor (IZA), 2009)
Portuguese firms engage in intense reallocation, most employers simultaneously hire and separate from workers, resulting in a large heterogeneity of flows and excess turnover. Large and older firms have lower flows, but high excess turnover rates. In small firms, hires and separations move symmetrically during expansion and contraction periods, on the contrary, large firms adjust their employment levels by reducing entry and not by increasing separations. Most hires and separations are on fixed-term contracts and shrinking firms replace a larger share of their separations under fixed-term contracts, while expanding firms replace most of the separations under open-ended contracts. The comparison with the U.S. shows that while worker and job flows are lower in Portugal, the excess turnover is remarkably close in the two countries.
Keywords: J21; J23; J63; 330; Job flows; worker flows; excess turnover; fixed-term contracts; firm size; Arbeitsmobilität; Arbeitsnachfrage; Personalabbau; Betriebsgröße; Beschäftigungseffekt; Portugal